Irreversible morphological changes contributing to depressed cardiac function after surgery for chronic aortic regurgitation. Issue 6 (December 1982) - Donaldson, R M; Florio, R; Rickards, A F; Bennett, J G; Yacoub, M; Ross, D N; Olsen, E
Abstract : The timing of surgery in chronic aortic regurgitation remains a difficult problem. To identify variables predictive of postoperative haemodynamic improvement, changes in left ventricular mass, volume, morphology, and histochemistry were analysed in 67 patients undergoing surgery for chronic aortic regurgitation. Patients were divided into two groups: those in whom the left ventricular echo diameters returned to normal after operation (51 patients, group A), and those with postoperative dilatation (16 patients, group B). A preoperative biopsy was obtained in all patients; postoperative tissue samples were available in 13 patients (five from group A, eight from group B). Data were correlated with the postoperative clinical, haemodynamic state over a follow-up period of three years. Regression of hypertrophy was usually incomplete. Echocardiographic and angiographic data could not define the type and degree of dysfunction which was irreversible. Massive fibre hypertrophy (mean 34.1 micrometers), moderately or severely increased interstitial fibrous tissue, reduced levels of the myofibrillar and mitochondrial enzymes adenosine triphosphates and succinate dehydrogenase in pre- and post-operative tissue samples correlated with persistent dilation, cardiac failure, and early death (group B). Irreversible morphological and functional changes contributed to a depressed cardiac function after operation. Preoperative ventricular biopsies are thus of prognostic importance in volume overload.